PSYCHOSOCIAL AND INTERPERSONAL FACTORS INFLUENCING DIABETES SELF-MANAGEMENT: THE ROLES OF SELF-EFFICACY, PSYCHOLOGICAL STRESS, FAMILY SUPPORT, AND HEALTHCARE COMMUNICATION - Eliza Zihni Zatihulwani; Kusuma Wijaya Ridi Putra; Karisma Dwi Ana (Universitas Nahdlatul Ulama Surabaya, 2026)
Background: Diabetes mellitus is a major global health challenge requiring lifelong self-management. Optimal diabetes self-management is influenced not only by clinical factors but also by psychosocial and interpersonal aspects, including self-efficacy, psychological stress, family support, and healthcare communication. Objective: This study aimed to analyses the influence of psychosocial and interpersonal factors on diabetes self-management among patients with Type 2 Diabetes Mellitus (T2DM). Methods: A cross-sectional analytical study was conducted among 50 T2DM patients at RSUD Jombang from January to March 2025. Data were collected using validated instruments, including the Summary of Diabetes Self-Care Activities (SDSCA), Diabetes Management Self-Efficacy Scale (DMSES), Perceived Stress Scale (PSS-10), Multidimensional Scale of Perceived Social Support (MSPSS), and a healthcare communication questionnaire. Data analysis included descriptive statistics, correlation tests, and multiple linear regression. Results: Self-efficacy showed a significant positive correlation with diabetes self-management (r = 0.521; p = 0.001), while psychological stress showed a significant negative correlation (r = -0.463; p = 0.002). Family support (r = 0.487; p = 0.001) and healthcare communication (r = 0.455; p = 0.003) were positively associated with self-management. Multiple regression analysis revealed that all variables significantly influenced diabetes self-management, with self-efficacy as the strongest predictor (β = 0.41; p = 0.002). The model explained 50.7% of the variance. However, this study is limited by its cross-sectional design, small sample size, and reliance on self-reported data, which may affect generalizability and causal interpretation. Conclusion: Psychosocial and interpersonal factors significantly influence diabetes self-management. Interventions should focus on improving self-efficacy, reducing stress, enhancing family support, and strengthening healthcare communication to improve patient outcomes.